Second Progress Report On Inclusion of Enhanced Contractual Provisions in International Sovereign Bond Contracts. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2016)
endorsed in October 2014 the inclusion of key features of enhanced pari passu provisions and collective action clauses (CACs) in new international sovereign bonds. Specifically, the Executive Board endorsed the use of (i) a modified pari passu provision that explicitly excludes the obligation to effect ratable payments, and (ii) an enhanced CAC with a menu of voting procedures, including a 'single-limb' aggregated voting procedure that enables bonds to be restructured on the basis of a single vote across all affected instruments, a two-limb aggregated voting procedure, and a series-by-series voting procedure. Directors supported an active role for the IMF in promoting the inclusion of these clauses in international sovereign bonds. The IMFC and the G20 further called on the IMF to promote the use of such clauses and report on their inclusion. In September 2015, the IMF published a progress report on the inclusion of the enhanced clauses in international sovereign bonds as of end-July 2015. The report found that since the Executive Board's endorsement, substantial progress had been made in incorporating the enhanced clauses: 41 issuances, representing 60 percent of the nominal principal amount of total issuances, had included the enhanced clauses as of July 31, 2015. The 2015 paper also provided initial observations on the patterns of incorporation, the market impact of inclusion of the enhanced clauses, and an update on the outstanding stock of international sovereign bonds. This paper provides a further update on the inclusion of the enhanced clauses and on the outstanding stock of international sovereign bonds as of October 31, 2016. Section II reports on the inclusion of these enhanced provisions, finding that uptake of the clauses has continued, with only a small minority of new issuances not including them. Section III provides an update on the outstanding stock, which reveals that while an increasing percentage of the outstanding stock includes enhanced clauses, a significant percentage of the stock still does not. Section IV reports on the use of different bond structures, and Section V describes the staff's ongoing outreach efforts. Section VI briefly reports on other recent developments relevant to the contractual approach to sovereign debt restructuring and Section VII concludes with next steps.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet